Magnitude and attributed reasons for adult weight gain amongst women at increased risk of breast cancer - Mary Pegington; Elaine F. Harkness; Anthony Howell; D. Gareth Evans; Michelle Harvie (BMC, 2022)
Abstract Background Excess weight (BMI ≥25.0 kg/m2) and weight gain during adult life increase the risk of postmenopausal breast cancer in women who are already at increased risk of the disease. Reasons for weight gain in this population can inform strategies for weight gain prevention. Methods Baseline data from six weight loss studies for women at increased risk of breast cancer (age 31-74 years) were collated. Self-reported patterns of adult weight gain and attributed reasons for weight gain before joining the weight loss study were reported for the whole population and secondary analyses reported the different reasons given by women with/without children, pre−/peri- or postmenopausal, and moderate/high risk of breast cancer. Results Five hundred and one women with a mean age of 47.6 (SD 8.4) years and median BMI of 29.9 (IQR 27.0-34.7) kg/m2 were included in the analyses. The median weight gain since young adulthood (18-20 years) was 20.5 (IQR 14.0-29.7) kg or 33.7 (23.4-50.2) % and median annual weight gain was 0.73 (IQR 0.51-1.08) kg. Four hundred and one women were included in analysis of weight gain reasons. The main five self-reported reasons for weight gain were children / childcare / pregnancy (stated by 55.9% of participants), followed by inactivity (41.9%), comfort or boredom eating (38.2%), portion size (32.4%), and stress (27.4%). Reasons appeared broadly similar between the different groups in the secondary analyses. Conclusions We have highlighted common reasons for weight gain in women at increased risk of breast cancer. This will inform future interventions to support women to avoid weight gain in adulthood which would reduce the burden of breast cancer. Trial registration NIHR NRR N0226132725, ISRCTN52913838, ISRCTN77916487, ISRCTN91372184, ISRCTN10803394 and ISRCTN16431108.